2000
DOI: 10.1152/ajpgi.2000.279.1.g192
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of gastric ulcers and diarrhea with the Amazonian herbal medicine sangre de grado

Abstract: Sangre de grado is an Amazonian herbal medicine used to facilitate the healing of gastric ulcers and to treat gastritis, diarrhea, skin lesions, and insect stings. This study was designed to evaluate the gastrointestinal applications. Gastric ulcers were induced in rats by brief serosal exposure of the fundus to acetic acid (80%). Sangre de grado was administered in drinking water at 1:1,000 and 1:10,000 dilutions from the postoperative period to day 7. Guinea pig ileum secretory responses to capsaicin, electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 23 publications
3
44
0
6
Order By: Relevance
“…In addition to these well-known effects on sensory nerves, capsaicin has been used as a diarrhea-inducing reagent in in vitro systems (Moriarty et al, 2001). This latter effect of capsaicin may be independent of its action on nerve cells (Miller et al, 2000). The topology of VR1 shows a characteristic transmembrane domain that contains six putative ␣-helices.…”
Section: ϩmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to these well-known effects on sensory nerves, capsaicin has been used as a diarrhea-inducing reagent in in vitro systems (Moriarty et al, 2001). This latter effect of capsaicin may be independent of its action on nerve cells (Miller et al, 2000). The topology of VR1 shows a characteristic transmembrane domain that contains six putative ␣-helices.…”
Section: ϩmentioning
confidence: 98%
“…Although those complications are mainly associated with steatorrhea resulting from the deficiency of pancreatic enzyme secretion to digest fat (Rubinstein et al, 1986), the impaired fluid secretion caused by defects of Cl Ϫ transport in the intestinal epithelia also may play a pathophysiological role in gastrointestinal symptoms of CF patients (Gabriel et al, 1994;Binkovitz et al, 1999). On the other hand, capsaicin has been reported to cause diarrhea by increasing fluid secretion accompanied with stimulation of intestinal ion transport (Miller et al, 2000). It has been suggested that the mechanism for capsaicin-activated ion transport may involve stimulations of the sensory neurons to release neurotransmitters such as substance P and neurokinin (Vanner and MacNaughton, 1995;Moriarty et al, 2001).…”
Section: Capsaicin On Cftr Chloride Channel 1421mentioning
confidence: 99%
“…1 Extracts (or infusions) of the different parts of the plant of several species of the genus Croton as C. lechleri, C. palanostigma, C. draconoides and C. urucurana are traditional remedies well known for their healing powers and are extensively used by indigenous cultures of the Amazon River for the treatment of infected wounds and to hasten wound healing. [2][3][4][5][6][7][8] Its stem bark, when slashed, releases a blood-red sap and, for this reason, C. urucurana and other species of the genus Croton are known as Dragon's Blood (or Sangra d'água in Brazil).…”
Section: Introductionmentioning
confidence: 99%
“…Existen varios estudios fitoquímicos (7,8) y farmacológicos realizados en el extranjero y nacionales, en los que nuestro equipo ha contribuido con investigaciones que reconocen su valor protector en la mucosa gástrica de ratas, tanto de la resina como de su fracción alcaloidea denominada taspina (9)(10)(11) ; asimismo, se ha profundizado en cierto grado sobre su probable mecanismo de acción (12)(13)(14) . También, se ha realizado evaluaciones preclínicas que han validado sus propiedades cicatrizantes en la piel de animales de experimentación (3,15,16) y se ha estudiado su potencial toxicológico (11,(17)(18)(19)(20)(21) .…”
Section: Introductionunclassified
“…También, se ha realizado evaluaciones preclínicas que han validado sus propiedades cicatrizantes en la piel de animales de experimentación (3,15,16) y se ha estudiado su potencial toxicológico (11,(17)(18)(19)(20)(21) .…”
Section: Introductionunclassified